A Natural Polymer Modified Separator as a Barrier in Lithium‐Sulfur Batteries to Inhibit the Shuttle of Polysulfides. Issue 7 (8th June 2022) - Xie, Dongming; Zuo, Xiaoxi; Su, Zhuoying; Zhu, Tianming; Liu, Shuang; Xiao, Xin; Nan, Junmin
Abstract : Lithium–sulfur batteries receive widespread attention in the past decade as a result of their high theoretical specific capacity. However, the shuttle effect of soluble polysulfides produced in the battery cycle can result in low sulfur utilization and slow reaction kinetics, which seriously hinders its practical application. Herein, a carrageenan (CG)–acetylene black (AB)‐modified separator for long‐life Li–S batteries is proposed. The batteries with modified separator exhibit excellent electrochemical performance, fast redox kinetics (733 mAh g −1 at 6 C), and a low‐capacity decay of 0.042% per cycle at 2 C. More importantly, a high reversible capacity of 805 mAh g −1 can be obtained at a high sulfur loading of 3.2 mg cm −2 . The performance improvement of the separator can be attributed to the outstanding adsorbing polysulfides ability of CG and the better conductivity of AB. Combined with the natural source of CG, simple preparation process, and excellent electrochemical performance, our research results provide a kind of Li–S batteries promising modification idea. Abstract : A carrageenan (CG)–acetylene black modified separator for long‐life Li‐S batteries is proposed. The batteries with modified separator exhibit excellent electrochemical performance such as a low‐capacity decay of 0.042% per cycle at 2 C. Combined with the natural source of CG and simple preparation process, our research results provide a promising idea for the modification of Li‐S batteries.